Ferromagnetic Behavior of Fe+ Implanted Si(100) Semiconductor - (:unkn) unknown (SPRINGER, 2012)
Fe ions have been implanted into Si (100) single crystals using ion implantation technique. The Fe ions have been accelerated to 45 keV with a dose of 5x10(17) ion/cm(2) at room temperature. The ions have been sent to the substrate's surface at normal incidence. The temperature dependence of magnetization measurement was explored at the temperature range of 10-300 K. The implanted Si substrate was studied with Ferromagnetic Resonance (FMR) technique and Vibrating Sample Magnetometer (VSM). The FMR spectra were recorded by applying external magnetic field in different experimental geometries. FMR spectra were analyzed and the magnetic properties, which are the g-factor, effective magnetization and uniaxial anisotropy parameter, were estimated by simulation of the experimental data. The sample showed two-fold magnetic anisotropic symmetry. By fitting the Si-2p region obtained through XPS measurements it is observed that Fe and Fe compounds are present in the material.
Keywords: Ion implantation; Iron; Silicon; Ferromagnetic resonance; Magnetic properties; Uniaxial anisotropy; HEUSLER ALLOY-FILMS; GILBERT DAMPING CONSTANT; ION-IMPLANTATION; SPINTRONICS